Feasibility of ultrafast DCE-MRI for identifying benign and malignant breast lesions - Huang, Junhui; Ao, Yongsheng; Mu, Lan; Zhao, Jierui; Chen, Hongliang; Yang, Long; Yao, Bingyu; Zhang, Shuheng; Yang, Shimin; Mok, Greta S. P.; Zhang, Ke; Hu, Zhanli; et al. (Computerized medical imaging and graphics, 2025)
Objectives - This study investigates whether the use of ultrafast DCE-MRI immediately after contrast injection is an alternative to conventional DCE-MRI for diagnosing benign and malignant breast lesions. - Methods - A total of 86 female patients were included in this prospective study. Each patient underwent both ultrafast DCE-MRI and conventional DCE-MRI before surgery. The Mann-Whitney U test was used to analyze whether there were significant differences in DCE-MRI parameters between benign and malignant breast lesions (p<0.05) for both conventional and ultrafast methods. The AUC value of the ROC curve was used to assess the diagnostic performance for each parameter and to determine their critical values, sensitivity, and specificity using the maximum Youden index. Delong test and support vector machine (SVM) were also used to evaluate the performance of conventional DCE-MRI and ultrafast DCE-MRI in identifying benign and malignant breast lesions. - Results - A total of 99 lesion areas (21 benign and 78 malignant lesions) were found in the 86 patients. Conventional DCE-MRI has only two semiquantitative parameters that can identify benign and malignant (Wash-out and SER, p<0.05), whereas ultrafast DCE-MRI is the one that can identify benign and malignant for all semiquantitative parameters except clearance, and there are more semiquantitative parameters that can be used to identify benign and malignant by ultrafast DCE-MRI than by conventional DCE-MRI. The ultrafast DCE-MRI parameters (AUC=0.8626) had a greater AUC than the conventional DCE-MRI parameters (AUC=0.7552) for distinguishing between benign and malignant breast lesions. - Conclusions - Ultrafast DCE-MRI is effective in identifying benign and malignant breast lesions at the early stage of contrast injection; therefore, it is feasible to use Ultrafast DCE-MRI instead of conventional DCE-MRI to diagnose benign and malignant breast tumor lesions. - Advances in knowledge - We evaluated ultrafast DCE-MRI's quantitative parameters in distinguishing benign from malignant breast lesions. SVM was used to assess the performance of conventional and ultrafast DCE-MRI in breast malignancy discrimination.